DIGITAL STORY: AN EFFECTIVE MEDIA TO TEACH LISTENING FROM THE PERSPECTIVE OF STUDENTSâ SCHEMATA - Sari, Dwi Rosita (English Teaching Journal, 2013)
The objectives of this research are to identify the effectiveness of Digital Story Media in teaching listening, and whether there is an interaction between the media and studentsâ schemata. This experimental study was conducted at a university in Madiun, East Java.The population was the second semester students of this university in the academic year of 2012/2013. Cluster random sampling was used to select 132 students for obtaining two classes of sample and they are randomly classified into two groups: experimental and control group. The instruments of this research were listening test and studentsâ schemata questionnaire. The data were analyzed using Liliefors and Bartlete tests to investigate the normality and the homogeneity of the data. After that, ANOVA and TUKEY tests were used to test the hypotheses. The research findings show that: (1) Digital Story Media is more effective than Animation Video in teaching listening; (2) the students having high schemata have better listening skill than the students having low schemata; and (3) there is an interaction between teaching media and studentsâ schematain teaching listening. That Digital Story Media is effective to teach listening, however teachers are suggested to improve the studentsâ schemata because it affects students listening achievements.Key words: Digital Story Media, animation video, studentsâ schemata, listening, experimental study.